Implementation of the Think Pair Share Cooperative Learning Model to Improve Student Learning Achievement in Science Subjects - Nani Arini (Saniya Institute, 2024)
The use of cooperative learning models has become a major focus in educational research due to its potential in improving student learning achievement. This study aims to investigate the effectiveness of Think Pair Share (TPS) cooperative learning model in improving students' learning achievement in Science subject. This study used a quantitative approach with a quasi-experimental design. The study population was 5th grade students in X city, with two classes as samples. Data were collected through learning achievement tests before and after the application of the TPS model. The analysis results showed a significant increase in students' learning achievement after the implementation of the TPS model. In conclusion, the TPS model is effective in improving students' learning achievement in science subjects. This research provides practical insights for educators seeking effective strategies to improve student learning achievement.